Tocolytic effect of combined sildenafil citrate and nifedepine versus nifedipine alone for management of preterm labour at a tertiary centre - Karya, Urmila; Rani, Anupam; Srivastava, Anshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was conducted to evaluate tocolytic effect of sildenafil citrate and nifedipine versus nifedipine alone for management of preterm labour. Methods: Prospective randomized study on 80 women aged 18-35 years with singleton pregnancy of 28-34 weeks gestation with preterm labour, fulfilling the inclusion criteria were randomly divided in two groups of 40 each. In regimen A women were given sildenafil citrate and nifedipine while in regimen B nifedipine alone for 72 hours as tocolysis. Results: Higher mean latency in sildenafil and nifedipine combination regimen compared to nifedipine alone regimen (28.23±18.3 versus 12.98±13.35 days, p<0.001). In regimen A, less days of hospital stay (3.23±0.92 versus 3.9±0.38 days, p<0.0001); improve perinatal outcomes in form of fewer deliveries during hospitalization or within 7 days after discharge (p=0.018); reduction in NICU admission (0.68±1.54 versus 3.18±4.61 days, p=0.002); improvement in birth weight (p<0.001) and fewer neonatal complications. Only minor side-effects like facial flushing (42.5% versus 22.5%, p=0.029), headache (40% versus 25%), dyspepsia (15% versus 2.5%, p=0.047), nasal congestion, palpitation, hypotension, constipation, nausea, dizziness were seen. Conclusions: Our study found combination of sildenafil citrate with nifedipine as superior and successful regimen with future potential as a tocolytic therapy.